Improving Students’ Focus and Participation through the Use of Interactive Videos in Narrative Text Learning in Class X-2 of SMAN 17 Surabaya - Juliarni Nalisaputri; Wijayadi; Nur Fitriah (PROCEEDING UMSURABAYA, 2026)
This study aims to enhance students' focus and participation in learning Narrative Text through the implementation of interactive video media. The research employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects of this study were 36 tenth-grade students of SMAN 17 Surabaya. Data were collected using observation sheets designed to assess two main aspects: students’ focus and participation during the learning process. The results showed that in the first cycle, the average student focus reached 79.44% (categorized as good), while participation was 75% (categorized as fair). After improving the strategy in the second cycle, the results increased to 80% for focus and 78.33% for participation, both categorized as good. These improvements indicate that the use of interactive video media with appropriate duration, engaging storyline, and embedded critical questions can significantly enhance students' cognitive and affective engagement. These findings emphasize the importance of integrating interactive learning media supported by appropriate teaching strategies and the active role of teachers in creating an engaging and participatory learning environment.